Increased Motivation To Learn By Using Learning Model Learning Community Students Mathematics Education - Sumargiyani Sumargiyani; Habibi Habibi; Bidayatun Nafi’ah (Journal of Disruptive Learning Innovation (JODLI), 2020)
This Research aims to increase the motivation of students in differential calculus learning using the Learning Community model in the class B Mathematics Education Program of Ahmad Dahlan University academic year 2018/2019, totaling 28 students. This type of research is a class action study consisting of planning, action, observation, and reflection phases. The instrument used in this study is an observation sheet. The results showed that the student's learning motivation increased as demonstrated by the increased motivation of learning students from Cycle 1 which was 76.5 percent in the high category, while in Cycle 2 increased to 81.5 percent in the class very High. It can be concluded that using learning Model Learning Community can improve the cultivation of teaching differential calculus of class B students UAD mathematics education.